Respuesta :

Answer:

(c) [tex]x = 0.6[/tex] and [tex]x = 0.7[/tex]

(d) [tex](x,y) = (0.67,2.33)[/tex]

Step-by-step explanation:

Given

See attachment

First, we complete the table

[tex]y = -x + 3[/tex]                                               [tex]y = 2x + 1[/tex]

[tex]y = -0.6 + 3 = 2.4[/tex]                                   [tex]y = 2 * 0.6 + 1 = 2.2[/tex]

[tex]y = -0.7 + 3 = 2.3[/tex]                                   [tex]y = 2 * 0.7 + 1 = 2.4[/tex]

[tex]y = -0.8 + 3 = 2.2[/tex]                                   [tex]y = 2 * 0.8 + 1 = 2.6[/tex]

[tex]y = -0.9 + 3 = 2.1[/tex]                                   [tex]y = 2 * 0.9 + 1 = 2.8[/tex]

So, we have:

[tex]\begin{array}{ccc}x & {y = -x + 3} & {y = 2x + 1} & {0.5} & {2.5} & {2} & {0.6} & {2.4} & {2.2} & {0.7}&{2.3} & {2.4} & {0.8}&{2.2} & {2.6} & {0.9}&{2.1} & {2.8} & {1}&{2} & {3} \ \end{array}[/tex]

Solving (c): Between which values is y

The values of y are for both equations are closest at:

[tex]x = 0.6[/tex] and [tex]x = 0.7[/tex]

Hence, the solution is between

[tex]x = 0.6[/tex] and [tex]x = 0.7[/tex]

Solving (d): Approximated value of the solution

We have:

[tex]y = -x + 3[/tex]

[tex]y = 2x + 1[/tex]

[tex]y=y[/tex]

So:

[tex]-x + 3 = 2x + 1[/tex]

Collect like terms

[tex]2x + x = 3 - 1[/tex]

[tex]3x= 2[/tex]

Divide both sides by 3

[tex]x = 0.67[/tex]

Substitute [tex]x = 0.67[/tex] in [tex]y = -x + 3[/tex]

[tex]y =-0.67 + 3[/tex]

[tex]y =2.33[/tex]

So, the solution is:

[tex](x,y) = (0.67,2.33)[/tex]

ACCESS MORE